2004
DOI: 10.1111/j.1600-0463.2004.apm1120106.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated decline in Helicobacter pylori seroprevalence rate during the screen and treat project in Vammala, Finland, as demonstrated in 29‐ to 45‐year‐old pregnant women

Abstract: The potential preventability of serious helicobacter-associated diseases - especially gastric cancer - has evoked interest in eradicating this pathogen from the population. We assessed the efficacy of the pioneering screen and treat intervention project in Vammala by studying helicobacter seroprevalence in pregnant women representing the normal population. Consecutive maternity clinic samples from native Finnish females at five different localities in 1995 (n=701) and 2000 (n=772) were investigated for class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Our previous study in 1993 showed that the density of living conditions was the prime determinant in the acquisition of H. pylori infection in Guangzhou city [8]. With the improvement of socioeconomic conditions and hygiene, H. pylori infection rates present decreasing trends in many regions all over the world, especially in some developing countries [12,19–22]. Such a decreasing trend also presented in our study carried out in Guangzhou city during a time span of 10 years.…”
Section: Discussionsupporting
confidence: 75%
“…Our previous study in 1993 showed that the density of living conditions was the prime determinant in the acquisition of H. pylori infection in Guangzhou city [8]. With the improvement of socioeconomic conditions and hygiene, H. pylori infection rates present decreasing trends in many regions all over the world, especially in some developing countries [12,19–22]. Such a decreasing trend also presented in our study carried out in Guangzhou city during a time span of 10 years.…”
Section: Discussionsupporting
confidence: 75%
“…In many developed countries, the overall prevalence of H. pylori infection has fallen dramatically over recent decades, such as in the Netherlands [8,9], Finland [10,11], the UK [12,13], Germany [14], or Greece [15], and the relatively low rate of infection in young people in developed countries is thought to be due largely to improved housing conditions during this century [16].…”
mentioning
confidence: 99%
“…On the basis of this active intervention, the initial H. pylori seroprevalences were calculated to have markedly decreased in the pilot study and in the populationbased studies. This was further supported by a survey in maternity clinics in six Finnish communities, including Vammala, showing that only in Vammala a significant decline in the prevalence rate of H. pylori antibodies from 1995 to 2000 was seen [20]. We started the program before the first European guidelines for the management of H. pylori infection were published [21].…”
Section: Discussionmentioning
confidence: 94%